Corporate Governance and Market-Based Value in ESG-Adopted Firms: The Moderating Role of Institutional Ownership - Asma’ul Azizah; Andri Prastiwi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study investigates the relationship between corporate governance and market-based firm value in ESG-adopted firms listed on the Indonesia Stock Exchange between 2019 and 2023, and examines the moderating role of institutional ownership. The analysis employs panel data regression with a sample of 161 companies, using variables measured by Tobin's Q, Bloomberg Governance Performance Score, and institutional ownership percentage. The results indicate that corporate governance has a significant positive effect on firm value. Control variables reveal that growth and profitability positively influence firm value, while leverage and firm size have negative effects. However, institutional ownership does not significantly moderate the governance-value relationship. The findings highlight that robust governance practices play a crucial role in enhancing firm value in ESG-adopted Indonesian companies, regardless of institutional monitoring mechanisms